2013
DOI: 10.1002/jcph.219
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of famotidine and ranitidine in critically ill children

Abstract: To characterize and compare acid suppression (pharmacodynamics) and pharmacokinetics of IV famotidine and ranitidine in critically ill children at risk for stress gastritis. Single-blind, randomized study in PICU patients 6 months to 18 years requiring mechanical ventilation with continuous gastric pH monitoring, randomized to IV famotidine 12 mg/m(2) or ranitidine 60 mg/m(2) when gastric pH < 4.0 >1 hour with serial blood sampling following first dose. Twenty-four children randomized to either famotidine (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The result interpretation and documentation of the pH were the responsibility of the bedside nurse, which encompassed a large group of health care providers and a potentially greater range of error. 5,6,8,17 Despite this, our results are in concert with these previous studies. Our study reflects the practice of monitoring gastric pH that is common in pediatric intensive care and would likely be used to titrate therapy, as opposed to more invasive monitoring.…”
Section: Figuresupporting
confidence: 89%
See 2 more Smart Citations
“…The result interpretation and documentation of the pH were the responsibility of the bedside nurse, which encompassed a large group of health care providers and a potentially greater range of error. 5,6,8,17 Despite this, our results are in concert with these previous studies. Our study reflects the practice of monitoring gastric pH that is common in pediatric intensive care and would likely be used to titrate therapy, as opposed to more invasive monitoring.…”
Section: Figuresupporting
confidence: 89%
“…However, prior pharmacokinetic studies have not shown significant differences in volume of distribution with increasing age. 3,5,6,9 This finding should be noted by clinicians and investigated further to determine the etiology of elevated gastric pH values in older critically ill pediatric patients.…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…At the present time, among all H2RAs, famotidine is preferred and commonly used because of its effectiveness in reducing stomach acidity [55,56]. However, its effect on human semen quality and sperm function is still undetermined.…”
Section: Effect Of Famotidinementioning
confidence: 99%
“…The ease of dosing, superior safety profile and less probability for drug-drug interaction has provided ranitidine an edge over its counterpart cimetidine 6 . Ranitidine is indicatedin GERD, gastric ulcers, Zollinger-Ellison syndrome and hyper-secretory states 7 .…”
Section: Introductionmentioning
confidence: 99%